Alokasi Optimal DG Sumber Energi Terbarukan Menggunakan Algoritme Multi-Verse Optimizer - Firdaus Firdaus; Ontoseno Penangsang; Rony Seto Wibowo; Umar (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
In the current situation, minimizing power loss in the distribution and transmission network is one of the research challenges. The distribution system has more losses than the transmission system. High power losses occur when loads connected to the distribution network are removed from the distribution substation. The optimal allocation for Distributed Generation (DG) renewable energy sources is one way to minimize distribution power loss and improve the distribution voltage profile. Inaccurate placement causes increased power losses, lowers the voltage profile and can adversely affect system performance. The Multi Verse Optimization (MVO) method is used to place DG renewable energy sources in the right location. In this work the MVO algorithm is implemented to optimize the location and type of DG for renewable energy sources. The implementation of the MVO algorithm was tested on the IEEE 33 bus radial distribution system. The results obtained indicate that the use of the MVO algorithm method for the optimal allocation of renewable DG is able to minimize power losses and increase the voltage profile.